Premises and Characteristics of "Contemporary Business" – the Context of Globalization, Internationalization and Threats - Glinkowska-Krauze, B.; Górecki, L.; Chebotarova, N. (Економічний вісник Донбасу, 2020)
In the course of previous comprehensive theoretical, methodological and empirical research of the authors, the main purpose of which was to identify ways of internationalization of Polish and Ukrainian enterprises. It was noted that a new model of business functioning is emerging, significantly different from the traditional model, in which the phenomenon of globalization underlies the process of internationalization of economic activity. At the same time, it should be borne in mind that the problem of studying specific practices of interaction between business structures in Poland and Ukraine, paradoxically, as a whole, is given insufficient attention (both in Polish and Ukrainian economic science). This served as the inspiration for writing this study, the main goal of which is to identify the features of the modern business model on the background of identifying the differences between the traditional and the current model in the context of existing threats and to find out the main (one of the main) reasons for such differences. The introduction refers to the methodology used for this study (specific research methods are methods of unity of analysis and synthesis, induction and deduction and comparative analysis, as well as methods of grouping and extrapolation). The study is the result of the authors' own empirical research and a comparative theoretical analysis based on the literature on the topic, and is a common characteristic of both models. In general terms, the main features of the modern business model and trends in the European economy are presented on the example of Poland and Ukraine. Thus, the study is aimed at identifying trends in doing business in the modern market and its characteristic features in the context of the predicted increase in the role of factors of intercultural (transcultural) interaction in business.